Estimation of soil loss by sheet and rill erosion in Perobas stream watershed (São Paulo State) in 1962 and 2011 - Demarchi, Julio Cesar [UNESP]; Piroli, Edson Luís [UNESP]; Zimback, Célia Regina Lopes [UNESP] (My University, 2019)
Soil erosion is one of the main forms of farming land degradation as it causes a negative impact on both food production and conservation of natural resources such as soil and water. The erosion quantification by means of modeling is essential for understanding and controlling the process. In this context, this paper aimed to estimate soil loss by erosion in Perobas stream watershed, located in Santa Cruz do Rio Pardo, São Paulo state, using the Revised Universal Soil Loss Equation (RUSLE), in 1962 and 2011, periods characterized by distinct land uses and management. The total soil losses were 49,130.37 ton in 1962 and 53,201.41 ton in 2011. Despite the implementation of support practices in 2011, which made the mean P factor to decrease from 0.786 to 0.466, and the improvement of crop management, there was a reduction in soil coverage by native forests and “campestre” formation (shrubs and sparse forest), with the consequent expansion of farming and livestock areas, the replacement of coffee crops by soybean and the increase of sugarcane and corn croplands. The Natural Potential of Erosion had a moderate correlation with the estimated erosion rates. The simulated erosion risk showed soil loss below tolerance, which ranges from 3.08 to 15.94 t.ha-1.yr-1 according to the soil type, in 74.09% and 75.14% of the study site in 1962 and 2011, respectively.
Estimativa de perda de solos por erosÃo laminar e linear na bacia hidrogrÁfica do ribeirÃo das Perobas (SP), nos anos 1962 e 2011
Keywords: Erosion modeling; Land use; RUSLE; Simulated erosion risk; Temporal analysis